Ewing sarcoma from molecular biology to the clinic - Dupuy, Maryne; Lamoureux, François; Mullard, Mathilde; Postec, Anaïs; Regnier, Laura; Baud’huin, Marc; Georges, Steven; Brounais-Le Royer, Bénédicte; Ory, Benjamin; Rédini, Françoise; Verrecchia, Franck (Frontiers in Cell and Developmental Biology, 2023)
In Europe, with an incidence of 7.5 cases per million, Ewing sarcoma (ES) is the second most common primary malignant bone tumor in children, adolescents and young adults, after osteosarcoma. Since the 1980s, conventional treatment has been based on the use of neoadjuvant and adjuvant chemotherapeutic agents combined with surgical resection of the tumor when possible. These treatments have increased the patient survival rate to 70% for localized forms, which drops drastically to less than 30% when patients are resistant to chemotherapy or when pulmonary metastases are present at diagnosis. However, the lack of improvement in these survival rates over the last decades points to the urgent need for new therapies. Genetically, ES is characterized by a chromosomal translocation between a member of the FET family and a member of the ETS family. In 85% of cases, the chromosomal translocation found is (11;22)(q24;q12), between the EWS RNA-binding protein and the FLI1 transcription factor, leading to the EWS-FLI1 fusion protein. This chimeric protein acts as an oncogenic factor playing a crucial role in the development of ES. This review provides a nonexhaustive overview of ES from a clinical and biological point of view, describing its main clinical, cellular and molecular aspects.